MODERN MICROBIOLOGICAL DIAGNOSIS OF VAGINAL CANDIDIASIS - Ra’no Sh. Boltayeva; Mushtariybonu A. Mamasoliyeva; Dilnura M. Tolkinjonova (Central Asian Journal of Medicine, 2024)
The modern microbiological diagnostic methods for Candida albicans, the most prevalent and active fungus in the vaginal microbiome of women, were analyzed. Based on laboratory examination results, diagnostic research conducted by the cultivation method is emphasized for practical use. Practical examples confirming the effectiveness of modern microbiological diagnostic methods are provided. Additionally, the integration of microbiological laboratory diagnostics is emphasized to improve women’s health and prevent vaginal diseases. This thesis explores one of the issues of microbiological diagnosis of vaginal Candida albicans within the integration of gynecology and microbiology. The importance of applying microbiological diagnostic methods in gynecological practice is also discussed.